DENATURATION OF LABEO ROHITHA (ROHU) ACTOMYOSIN ON FROZEN STORAGE PREVENTIVE EFFECT OF DI CARBOXYLIC ACID - RAO, S B (Fishery Technology, 2017)
The preventive effect of fumarate, maleate, tartrate and oxalate on the denaturation of frozen rohu actomyosin at-20oC in 0. 7 M KC1 for 7 weeks was examined using an in vitro test model. The rate of denaturation was followed by estimating percentage salt extractability, Ca2 + ATP-as activity and the clearing response test. Fumarate, maleate and tartrate showed cryoprotective effect for higher concentration of pre-rigor rohu actomyosin of 10 mg/ml and 20 mg/ml. At actomyosin concentration of 6 mg/ml, maleate and tartrate showed some preventive effect whereas fumarate enhanced denaturation. Oxalate showed poor cryoprotective action. Post-rigor rohu actomyosin was preserved frozen without denaturation to a greater extent than pre-rigor actomyosin.